2004
DOI: 10.1037/1528-3542.4.1.23
|View full text |Cite
|
Sign up to set email alerts
|

Identification Facilitation for Emotionally Arousing Verbs During the Attentional Blink.

Abstract: The present study aimed to examine affective modulation of the "attentional blink" effect during rapid serial visual presentation (RSVP). Pleasant, neutral, and unpleasant written verbs were used as a 2nd target (T2) in an 8.6-Hz RSVP paradigm. Pronounced effects of 1st target (T1)-T2 stimulus onset asynchrony (SOA) were found, showing reduced report accuracy for 232- and 464-ms SOAs. Affectively arousing (pleasant and unpleasant) T2s were associated with enhanced accuracy compared with neutral T2s specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
220
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(252 citation statements)
references
References 44 publications
(54 reference statements)
26
220
2
1
Order By: Relevance
“…Keil & Ihssen, 2004). Figures 1a and 1b set out the proportions of correctly identified T2s as a function of the experimental manipulations and participant group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Keil & Ihssen, 2004). Figures 1a and 1b set out the proportions of correctly identified T2s as a function of the experimental manipulations and participant group.…”
Section: Resultsmentioning
confidence: 99%
“…When T2 is emotionally charged, however, the AB phenomenon is attenuated (Keil & Ihssen, 2004), and this attenuation is thought to be mediated by a neural system involving the amygdala (Anderson & Phelps, 2001). …”
mentioning
confidence: 99%
“…As noted within the circumplex view of emotion (e.g., Posner, Russell, & Peterson, 2005;Russell, 2003), although emotional states such as those of being elated or upset can be characterised as possessing opposite valences, they can also be characterised as possessing comparable arousal levels. As stated earlier, despite some evidence against the hypothesis that arousal mediates the effects of positive and negative affect in cognition (Isen et al, 1987;Olivers & Nieuwenhuis, 2006), the results of a number of studies have provided support for this hypothesis (Anderson, 2005;Keil & Ihssen, 2004;Robinson et al, 2004;Schimmack, 2005). In the present paradigm, the results of Experiment 2 show that the effect of valence on perceptual flexibility could have been mediated by arousal at most only partially, not wholly, because positive and negative primes were matched on arousal, but nevertheless differed in their promotion of cognitive flexibility.…”
Section: Encouraging 25mentioning
confidence: 95%
“…These findings about the role of attention in binding suggest that emotionally arousing stimuli might be more effectively bound with their features in initial perception, insofar as they elicit more intense focused attention (for a review see Mather, 2007). Previous studies have shown enhanced initial perceptual processing for emotional stimuli, as they are more likely than nonemotional stimuli to be correctly identified when shown very briefly (Zeelenberg, Wagenmakers, & Rotteveel, 2006) and less likely to be missed when presented in a rapid serial visual presentation with other stimuli (Anderson, 2005;Keil & Ihssen, 2004). Brain imaging studies reveal that when shown a series of pictures, people show more activation in visual processing regions for emotionally intense pictures than for emotionally neutral pictures (Bradley et al, 2003;Phan et al, 2002;Mather et al, 2006).…”
Section: Mechanisms Of Arousal-enhanced Bindingmentioning
confidence: 97%